Ongoing Inversion of a Passive Margin: Spatial Variability of Strain Markers Along the Algerian Margin and Basin (Mediterranean Sea) and Seismotectonic Implications - Leffondré, Pierre; Déverchère, Jacques; Medaouri, Mourad; Klingelhoefer, Frauke; Graindorge, David; Arab, Mohamed (Frontiers in Earth Science, 2021)
Subduction initiation is an important but still poorly documented process on Earth. Here, we document one of a few cases of ongoing transition between passive and active continental margins by identifying the geometrical and structural signatures that witness the tectonic inversion of the Algerian continental margin and the deep oceanic domain, located at the northern edge of the slow-rate, diffuse plate boundary between Africa and Eurasia. We have analyzed and tied 7900 km of deep seismic reflection post-stacked data over an area of ~1200 km long and ~120 km wide. The two-way traveltime lines were converted into depth sections in order to reconstruct and map realistic geometries of seismic horizons and faults from the seafloor down to the acoustic basement. Along the whole length of this young transitional domain, we identify a clear margin segmentation and significant changes in the tectonic signature at the margin toe and in the deep basement. While the central margin depicts a typical thick- and thin-skinned tectonic style with frontal propagation of crustal thrust ramps, the central-eastern margin (Jijel segment) reveals a higher strain focusing at the margin toe together with the largest flexural response of the oceanic lithosphere. Conversely, strain at the margin toe is limited in the western margin but displays a clear buckling of the oceanic crust up to the Spanish margin. We interpret these contrasting, segmented behaviours as resulting from inherited heterogeneities in (1) the geometry of the Algerian continental margin from West to East (wrench faulting in the west, stretched margin elsewhere) and (2) the Miocene thermal state related to the diachronous opening of the Algerian basin and to the magmatic imprint of the Tethyan slab tearing at deep crustal levels. The narrow oceanic lithosphere of the Western Algerian basin is assumed to favor buckling against flexure. From the dimension and continuity of the main south-dipping blind thrusts identified at the margin toe, we reassess seismic hazards by defining potential lengths for ruptures zones leading to potential magnitudes up to 8.0 and 7.4 off the central and eastern Algerian margins, respectively.